Sound absorption of textile curtains – theoretical models and validations by experiments and simulations. Issue 1 (January 2018) - Pieren, Reto; Schäffer, Beat; Schoenwald, Stefan; Eggenschwiler, Kurt
Textile curtains can be designed to be good sound absorbers. Their acoustical performance, as usually described by the sound absorption coefficient, not only depends on the textile itself but also on the drapery fullness and the backing condition, that is, the spacing between the fabric and a rigid backing wall, or the absence of a backing in the case of a freely hanging curtain. This article reviews existing models to predict the diffuse-field sound absorption coefficient, which to date can only predict the case of flat curtains. A set of existing models is extended to the case of curtains with drapery fullness using a semi-empirical approach. The models consider different backing conditions, including freely hanging curtains. The existing and new models are validated by comparing predicted sound absorption coefficients with data measured in a reverberation room. Hereby, curtains consisting of different fabrics and with different degrees of fullness are considered. Besides situations with rigid backing, also the measurement data of textiles hung freely in space are included in this study. Comparisons reveal a very good agreement between measured and predicted sound absorption coefficients. Compared to currently available commercial sound absorption prediction software that can only handle the situation of flat textiles with rigid backing, the results of the presented models not only show a better agreement with measured data, but also cover a broader range of situations. The presented models are thus well applicable in the design and development of new textiles as well as in the room acoustical planning process.